Plasma homocysteine levels and associated factors in community-dwelling adolescents: the EVA-TYROL study - Gande, Nina; Hochmayr, Christoph; Staudt, Anna; Bernar, Benoît; Stock, Katharina; Kiechl, Sophia J.; Geiger, Ralf; Griesmacher, Andrea; Scholl-Bürgi, Sabine; Knoflach, Michael; Pechlaner, Raimund; Kiechl-Kohlendorfer, Ursula; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Homocysteine (Hcy) has been associated with an adverse cardiovascular risk profile in adolescents. Assessment of the association between plasma Hcy levels and clinical/laboratory factors might improve our understanding of the pathogenesis of cardiovascular disease. Methods Hcy was measured in 1,900 14- to 19-year-old participants of prospective population-based EVA-TYROL Study (44.3% males, mean age 16.4 years) between 2015 and 2018. Factors associated with Hcy were assessed by physical examination, standardized interviews, and fasting blood analysis. Results Mean plasma Hcy was 11.3 ± 4.5 µmol/L. Distribution of Hcy was characterized by extreme right skew. Males exhibited higher Hcy and sex differences increased with increasing age. Univariate associations with Hcy emerged for age, sex, body mass index, high-density lipoprotein cholesterol, and for factors pertaining to blood pressure, glucose metabolism, renal function, and diet quality, whereas the most important multivariate predictors of Hcy were sex and creatinine. Discussion Clinical and laboratory factors associated with Hcy in adolescents were manifold, with sex and high creatinine identified as strongest independent determinants. These results may aid when interpreting future studies investigating the vascular risk of homocysteine.